O poder da imagem fotográfica: uma análise das imagens publicadas nas revistas Veja e IstoÉ de Luiz Inácio Lula da Silva durante as campanhas presidenciais de 1989 e 2002 - Maranhão, Cristina (2007)
In the society which we live in, the images are everywhere and surround our social relationships. We define our relationships and opinions based on images. However, the excessive production of images creates a series of clichés that serve as a critical anesthesia that hinder us to perceive their discursive statements. Photography was a technique created in the beginning of the XIX century and its evolution is related to the technological advances of the Industrial Revolution, besides, it was present in the yearnings of the emergent bourgeoisie. Because of its possibility to produce copies and to serve as an evidential test of the reality, it has become synonymous of factual truth and soon it started to be used by some institutions as a way to legitimize their points of view. This work is an effort to focus on the power of the photographic images. When related to the medias, they receive new symbolic traits and start to constitute the ideological speech of each one. To comprehend this aspect of the image, an analysis of the photographic images used in the magazines Veja and IstoÉ during the presidential campaigns of the candidate Luiz Inácio Lula da Silva, in 1989 and 2002 has been done. Each historical moment and ideological line of each one of the magazines generated their own discursive statements, producing a characterization of the candidate. In the first campaign, Lula comes up as a promise to the left. Having a very different trajectory from his competitors, the candidate tries to fix an image that, in some ways, follows him up to the present. In his fourth attempt, he tries to deconstruct, to a certain extent, this image, in order to win the elections. Each magazine tried to portray a different Lula by using images and technical resources (diagramming, edition, legends). In some cases emphasizing his trajectory as metallurgist, someone related to the national left and trying to consolidate the image of the national elite nightmare, and at other moments trying to portray him as the ideal candidate to save the country